Ethnocentrism and Attitude of Jordanian Consumers towards Foreign Products - Albarq, Abbas N. (2009)
Consumer purchase behaviour toward foreign products has been for many years an area of ongoing interest in fields that span both consumer behavior and international marketing. This thesis, which is based on the concepts of Theory of Reasoned Action(TRA) and ethnocentrism (CET), has the following objectives, (1) measure the level of the consumer ethnocentrism among Jordanian consumer in Amman, (2)determinants that influence consumer behavior towards foreign products, (3) explain the structural interrelationships between the external variables conservatism, interest in travel within TRA model, (4) validate and generate a research model that will be able to demonstrate actual purchase consumer behaviour towards foreign products in Jordan. A questionnaire consisting of names of the variables (interest in foreign travel, conservatism, consumer ethnocentrism, attitude toward foreign product, intention toward foreign product, and actual purchase toward foreign product) was used to collect the data for this study. Phone calls were made to 518 households' respondents in Amman. This was done based on systematic random sampling using the telephone directory of Jordan (Yellow Pages). The survey yielded 382 usable questionnaires, with a response rate of 73.74%. Statistical analysis methods (SPSS) and Structural Equation Modelling (SEM) with AMOS version 7.0 were used to analyse data. The findings indicate that the level of ethnocentrism among Jordanian consumers in Amman is low, (2) all three predictors (conservatism, attitude toward foreign product, and intention) are significant factors influencing purchase behavior, (3) all direct relationships were supported, except interest in travel, (4) all indirect effects were supported, except that intention was not found to be a mediator between "ATT" and "ACT", (5) the TRA with external factors can partially explain the research model (interest in travel is not a significant factor affecting attitude), (6) the results showed that our modified model "GM" predicts Jordanian behavior to buy foreign product more effectively than the original TRA model. Using SEM, the Model Generating (MG) confirmed better fit and larger parsimony compared with the hypothesized (SC) and Alternative Model (AM), as shown in the GOF index, CMIN/df = 1.049; GFI = 0.940; RMSEA = 0.011; TLI = 0.999; P-value = 0.259; SMC = 0.77. This study has several valuable implications. Telephone survey used in this study could be considered as a big contribution. Most previous discussions on Jordanian CET were mainly journalistic account in nature or non-academic findings. They are economic experts who proclaimed in different occasion about there vision towards the Jordanian consumer preferences and the impact of these preferences. Our results contribute to the empirical research findings thus supporting narration and previous proclamations made by Jordanian writers. SEM is strongly recommended for better quality model testing and generating with AMOS software. The two external variables were added, which increased the power of the TRA model and helped towards the ongoing efforts of theory-building in this field. This approach should be continued in future research. In view of the low ethnocentrism, positive attitude and high intention toward foreign product among local consumers in Amman which increases the cash flow toward foreign product (high deficit), it would be appropriate to suggest the following recommendations: (i) an increase in import tariff will unambiguously lead to a general increase in price, since, in equilibrium, tariffs may be imposed to increase the cost of imported goods in relation to domestic production, thereby reducing the volume of imports and keeping the balance of payments in credit, or to protect domestic industry from foreign competition and will improve the demand on the home made products, (ii) launch a national campaign to increase the level and awareness of ethnocentrism among Jordanian consumers to encourage people to buy local and support local products Investigating the purchase behaviour toward foreign products based only on consumer perspective can be a limitation of this study. Future research can investigate such fields as business purchase behaviour or government purchase behaviour, which may have been neglected here.